Knowledge audit of Integrative Learning Intl role in integration of technology and business strategy - Penaflor, Maria Victoria; Talisayon, Serafin D. (University of the Philippines Diliman, Quezon City Technology Management Center, 2007)
A knowledge intensive firm such as IL International sees the need to create a knowledge management strategy to support its rapid business expansion. To jumpstart the KM initiative, I proposed a Knowledge Audit with the objective of identifying the company's existing knowledge assets and assess the company's information and knowledge policies, its knowledge structure and knowledge flow in relation to their business objectives. Effective strategies call for the integration of technology and incorporation of technological concerns into the strategies chosen for the business. Technology's most valuable role in knowledge management is broadening the reach and enhancing the speed of knowledge transfer. The ultimate goal of course is to make the company's KM system a solid, efficient and reliable vehicle for delivering knowledge to its knowledge professionals. The Knowledge Audit presents a baseline of knowledge assets at IL. I recommend that this be used in the codification approach for the knowledge management strategy.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Knowledge economy; Technology and business strategy; Information technology -- Management; Knowledge audit; Integrative Learning Intl